PERAN AKUNTANSI DI RUMAH SAKIT PEMERINTAH PASCA BADAN LAYANAN UMUM (BLU) DAN ADOPSI INDONESIAN CASE BASED GROUPS (INA-CBGS) (STUDI KASUS PADA RSUD DATU BERU TAKENGON) - Ikhwan Noviardi (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2020)
Abstract This study aims to discuss the role of accounting in the Datu Beru Takengon Regional Hospital after BLUD status and the adoption of INA-CBGs. The role of accounting in hospitals is reflected in accounting innovations and strategies in responding to INA-CBGs. For this reason, the focus of this study is to look at accounting innovation efforts and strategies to respond to INA-CBGs carried out by the management of Datu Beru Takengon Regional Hospital. The method used in this research is a qualitative method with a case study approach. Sources of data come from informants who are selected based on certain criteria (purposive sampling). The data collection technique in this study was an interview instrument. The type of interview is a semi-structured interview. The results of this study reveal that the role of accounting in the Datu Beru Takengon Regional Hospital has increased, especially after changes to the hospital payment system, namely, INA-CBGs. Meanwhile, the change in status to BLUD did not have a direct impact on changing the role of accounting. The change in the role of accounting at the Datu Beru Takengon Regional Hospital is reflected in the accounting innovation efforts undertaken by management by involving medical personnel, especially specialist doctors in accounting practice. These specialist doctors have been asked to calculate the unit cost of each medical service using the Activity Based Costing (ABC) method. In addition, doctors have also been asked to be more concerned about controlling the cost of medical services so that they do not exceed the INA-CBGs rate. Keywords: Accounting Role, BLUD Status, INA-CBG Adoption. Abstrak Penelitian ini bertujuan untuk mendiskusikan peran akuntansi di RSUD Datu Beru Takengon pasca status BLUD dan adopsi INA-CBGs. Peran akuntansi di rumah sakit tercermin dari inovasi akuntansi dan strategi dalam merespon INA-CBGs. Untuk itu, fokus penelitian ini adalah melihat upaya inovasi akuntansi dan strategi merespon INA-CBGs yang dilakukan manajemen RSUD Datu Beru Takengon. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi kasus. Sumber data berasal dari narasumber (informan) yang dipilih berdasarkan kriteria tertentu (purposive sampling). Teknik pengumpulan data dalam penelitian ini adalah dengan instrument wawancara. Jenis wawancaranya adalah wawancara semi terstruktur. Hasil penelitian ini mengungkap bahwa peran akuntansi di RSUD Datu Beru Takengon telah mengalami peningkatan terutama setelah perubahan sistem pembayaran rumah sakit yaitu, INA-CBGs. Sementara itu, perubahan status menjadi BLUD justru tidak berdampak langsung pada perubahan peran akuntansi. Perubahan peran akuntansi di RSUD Datu Beru Takengon tercermin dari adanya upaya inovasi akuntansi yang dilakukan oleh manajemen dengan melibatkan tenaga medis terutama para dokter spesialis dalam praktek akuntansi. Para dokter spesialis tersebut telah diminta untuk menghitung unit cost setiap jasa pelayanan medis dengan menggunakan metode Activity Based Costing (ABC). Selain itu, para dokter juga telah diminta untuk lebih peduli terhadap pengendalian biaya pelayanan medis agar tidak melebihi tarif INA-CBGs. Kata kunci: Peran Akuntansi, Status BLUD, Adopsi INA-CBGs